KARAKTERISASI KIMIA SUSU SAPI PERAH DI KABUPATEN SINJAI - Bagus Oka; Mohammad Wijaya; Kadirman Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2017)
The purpose of this research is to know the chemical characteristics of milk dairy cow in Sinjai District include fat content, protein content, calcium level and phosphorus level. The results of this test will be compared with the requirement of fresh milk quality based on Indonesian National Standard. This research is a kind of survey research, this research is done by taking samples of milk dairy cattle at three farmer groups in Sinjai District, especially in West Sinjai Sub-district namely  Batu leppa farmer group, Batu Pangkaiya  farmer group and Pattiroang farmer group. The results showed that milk protein content of dairy cows in Sinjai District has complied with Indonesian National Standard, but its fat content has not fulfilled the Indonesian National Standard. The calcium and phosphor content of dairy cattle milk in Sinjai District is good enough and meets the standards of fresh milk based on the Ministry of Health of the Republic of Indonesia